Non-Occlusive Retinal Vascular Inflammation and Role of Red Blood Cell Deformability in Birdshot Chorioretinopathy. (18th August 2019) - Agrawal, Rupesh; Ang, Bryan; Balne, Praveen Kumar; Richards, Christopher; Smart, Thomas; Cardoso, João; Shima, David; Jones, Philip H.; Pavesio, Carlos
ABSTRACT: Purpose : To investigate differences in red blood cell (RBC) deformability between birdshot chorioretinopathy (BCR) subjects and matched controls, and to postulate its relationship with lack of vascular occlusion in BCR. Methods : In a single center, prospective, non-randomized mechanistic study, blood samples were collected from eight healthy controls and nine BCR patients, and subjected to biochemical and hematological tests, as well as RBC indices assessment using dual-beam optical tweezers. Results : The mean age of the controls was 52.37 ± 10.70 years and BCR patients was 53.44 ± 12.39 years. Initial cell size ( I o ) for the controls was 8.48 ± 0.25 μm and 8.87 ± 0.31 μm for BCR RBCs ( p = 0.014). The deformability index (DI) for the controls was 0.066 ± 0.02 and that for BCR RBCs was 0.063 ± 0.03 ( p = 0.441). Conclusion : There was no statistically significant difference in DI between RBCs from BCR and healthy controls. This may explain the rare occurrence of retinal vascular occlusion despite the underlying vasculitic pathophysiology of BCR.